Investigating the antiferroelectric-ferroelectric phase switching time in lanthanum-modified lead zirconate titanate transparent ceramics by using the electrically induced light scattering effect. Issue 2 (February 2021) - Wang, Longhai; Wu, Yunyi; Liu, Feng; Wang, Shimin; Cao, Wanqiang; Pan, Ruikun; Sun, Zhengguang; Zheng, Keyu; Chen, Ming; Yang, Beibei; Ming, Xinghua; He, Xiyun
Abstract: A method for achieving the accurate measurement of the antiferroelectric-ferroelectric (AFE-FE) phase switching time based on the electrically induced light scattering effect was designed. The AFE-FE switching times of lanthanum-modified lead zirconate titanate (PLZT) transparent ceramics decreased with the increase of the applied electric fields, and the logarithm of the switching time was approximately proportional to the electric field reciprocal. The random orientation of the polycrystalline structures with dispersion-distributed mixed phases of the PLZT transparent ceramics was the intrinsic mechanism affecting the corresponding switching times in the applied electric field. The smaller electrode size samples switched faster than the larger samples in the same electric field. The size effect of the switching times occurred due to the higher dielectric constant of the ceramics and the parameters of the test circuit, and the larger capacitance of the samples resulted in a longer rising time of the applied electric field, which in turn slowed down the phase switching and prolonged the switching time.